Effects of Diffusion Welding Parameters on Microstructure and Properties of Al-Si-Al2O3 Alloys Joints - Jiang, Xiaosong; Li, Jingrui; Liu, Wanxia; Zhu, Degui; Wang, Bo (Asian Journal of Chemistry, 2014)
Aluminum matrix composite material of Al-5 % wtSi-Al2O3 is welded by diffusion welding. The effect of welding temperature, holding time, welding pressure and other welding parameters on properties and microstructure of welded joints of Al-5 % wt Si-Al2O3 is studied through analyzing mechanical property and microstructure. Results indicate that average shear strength of the welding joint is 25.45 % of the original strength at welding parameter of 555 ºC × 50 MPa×3 h which is the optimal value of Al-5 % wt Si-Al2O3 welded joint obtained using diffusion welding. Based on welding parameters on properties and microstructure of welded joints of Al-5 % wt Si-Al2O3, diffusion welding formation characteristics and mechanism of Al-Si-Al2O3 alloys have been analyzed and can be explained by diffusion theory.